Toxin A-deficient mutants of Pseudomonas aeruginosa PA103: isolation and characterization. - Ohman, D E (1980)
An immunological assay utilizing double-diffusion principles was developed for identification of Pseudomonas aeruginosa mutants deficient in toxin A. Mutations were chemically induced, and mutants were isolated from P. aeruginosa strain PA103. Quantitative assays, both enzymatic and immunological, indicated that five mutants produced toxin A in vitro at levels of 0.3% or less of parental strain levels. Characterization indicated that the mutants fell into four classes and suggested that multiple genes are involved in the regulation of toxin A yields. Classes 1 to 3 produced less than 1% of parental levels of extracellular toxin A. Class 1 mutants are apparently specific for toxin A. Class 2 mutants are pleotropic and produced toxin A, protease, and other extracellular proteins at reduced yields. Class 3 mutants are pleotropic and in addition have relatively high levels of cell-bound toxin A. Class 4 mutants produce toxin A at levels greater than 1% of parental yields. Of 16 toxin A-deficient mutants examined, only 1 was a class 1 mutant. This mutant (PA103-29) was shown to be identical to the parental strain in all respects tested except for its marked deficiency in toxin A. The suitability of this class 1 mutant for use in virulence studies is discussed.